PENGARUH MOTIVASI BELANJA HEDONIK DAN SUASANA TOKO TERHADAP PEMBELIAN IMPULSIF (Studi pada Konsumen Laris Toserba & Swalayan) - Catur Wulandari (STIE Rajawali Purworejo, 2024)
Modern retailers must have the right strategy so that consumers are interested in making purchases and especially consumers have impulsive purchases. There are several factors that can influence impulsive purchases, including hedonic and store atmosphere. Based on this, researchers are interested in conducting a study entitled